Research of the Microgeometry of the Surface of Cylinder Mirror of the Internal Combustion Engine (Texas Journal of Engineering and Technology, 2022)
The article covers the determination of optimal parameters of the mirror microgeometry of the cylinder of an internal combustion engine, as well as comparison of the microgeometry indicators of the cylinder mirrors of the internal combustion engine of the domestic manufacturer with the indicators of the world's leading representatives of car factories (Audi, Nisan).